EXPLORING THE APPLICATIONS OF CRISPR-CAS9 IN REVOLUTIONIZING AGRICULTURE FOR FOOD SECURITY AND SUSTAINABILITY - KARIM, A; AHMED, SF; ASAD, Z; SARWER, T; KANWAL, A; SHAINA, H; ISMAIL, A; SHAUKAT, S; MAJEED, F; TIPU, ALK (Biological and Clinical Sciences Research Journal, 2024)
CRISPR-Cas9 is a revolutionary gene-editing tool with the potential to transform agriculture by enabling precise modifications to plant genomes. This technology allows for the enhancement of critical crop traits, such as disease resistance, drought tolerance, and improved nutritional value, without introducing foreign DNA. It offers a faster, more cost-effective alternative to traditional breeding methods, contributing to food security in the face of climate challenges. One key application of CRISPR-Cas9 is its ability to improve crop resistance to pests and diseases, reducing reliance on chemical pesticides and promoting sustainable farming. It also holds promise for enhancing the nutritional content of crops and addressing global malnutrition. However, challenges remain, including ethical concerns, regulatory issues, and the need to assess the long-term environmental impacts of gene-edited crops. Despite these obstacles, CRISPR-Cas9 has the potential to revolutionize agriculture, and future research will focus on refining its precision and overcoming societal barriers. As these challenges are addressed, CRISPR-Cas9 could play a central role in developing resilient, sustainable crops for a growing global population.